The Effect Of Working Capital And Liquidity On The Profitability Of Companies In The Infrastructure Sector That Are Listed On The Bei In The Period 2020-2023 - Meiman Kristian Putra Gulo; Marshanda Marshanda; Febriani Nur Rahman; Indah Lestari; An Suci Azzahra (International Journal of Economic Research and Financial Accounting, 2025)
The State Defense System is directed towards fulfilling the basic minimum needs, or Minimum Essential Force (MEF). MEF is one of the targets of the National Medium-Term Development Plan (RPJMN) in the field of defense, divided into three stages. In the Master Plan for Defense Industry Development, the target of MEF phase III is to support the ideal posture, creating growth in the defense industry by 2029, and achieving Defense Industry Independence. This study aims to evaluate the MEF policy in realizing Defense Industry Independence so that it can become a pillar of sustainable defense economics. The research method used is qualitative with a literature study approach. This study uses the Evaluation Theory with the CIPP Model, where the research results show that: In the context evaluation, the MEF Policy emerges as a solution to realize the state's defense system towards the ideal posture to create Defense Industry Independence. In the input evaluation, it can be seen in the MEF Alignment process. In the process evaluation, it can be seen how MEF serves as a framework in realizing an independent defense industry so that it can become a pillar of sustainable defense economics through the Import Substitution Industrialization Policy and realizing downstream processes in the Defense Industry. Meanwhile, in the product evaluation, factors that hinder the realization of Defense Industry Independence were found. These factors include insufficient budget for domestic Defense Industry R&D compared to the budget for importing defense equipment from abroad, the lack of quality human resources, and funding limitations. To overcome these problems, a review of the performance of KKIP, as a state institution directly involved in overseeing the development of domestic defense equipment until 2029, is necessary